Improved magnetic properties in amorphous FeSiBCr soft magnetic composites with easy-plane anisotropy for high-frequency applications. (9th February 2023) - Huang, Yuandong; Zhang, Hang; Shang, Rongxian; Wang, Ke; Wu, Peng; Wang, Ying; Li, Fashen; Wang, Tao
Abstract: The miniaturization and high frequency of future electromagnetic devices require soft magnetic composites with high permeability, high working frequency, and low core loss. In this work, easy-plane amorphous FeSiBCr powders with a thickness of approximately 1–2 μ m are obtained by planetary ball milling, and are successfully fabricated into an arranged soft magnetic composite by using a uniform magnetic field. The complex permeability spectrums of the composites are measured and analyzed. Due to the planar distribution of easy magnetization axes, the amorphous easy-plane FeSiBCr/Si-resin composite shows a permeability of 31 at 1 MHz. The core loss of the samples is measured from 100 KHz to 5 MHz and is discussed in detail. The loss-separated results illustrate that the eddy current loss and excess loss can be effectively reduced in the amorphous easy-plane FeSiBCr/Si-resin composite. These results indicate that, compared with an amorphous non-easy-plane FeSiBCr/Si-resin composite, the permeability of the amorphous easy-plane FeSiBCr/Si-resin composite is effectively improved and the core loss is reduced, making it promising for high-frequency applications.